Political philosophy : the basics - Van der Vossen, Bas, 1979- (New York : Routledge, 2024)
"This book offers an introduction to political philosophy, the study of the role of government in our lives. It discusses what political philosophy is about, its most important and enduring questions, and how to do political philosophy well. Throughout the book discusses issues like: Do we have a moral obligation to obey the law? What's the value of equality? What's the nature of justice? How can we answer philosophical questions about politics? Is political philosophy a form of activism? Or is it more like a science? Written in an inviting and accessible style, Political Philosophy: The Basics offers an ideal starting point for anyone wishing to learn more about the philosophical study of politics"--
Introduction -- Starting political philosophy -- Political obligation -- Freedom and equality -- The social contract -- Justice -- Activism and philosophy.
Includes bibliographical references and index.
Keywords: Political science -- Philosophy; Political obligation; Liberty; Equality; Social contract; Justice; Activism